2018
DOI: 10.1016/j.ijhydene.2018.09.204
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alloying elements (Al, Mn, Ru) on desorption plateau pressures of vanadium hydrides: An experimental and first-principles study

Abstract: Vanadium-based alloys are promising for the reversible, compressed storage of renewable hydrogen. To improve the hydrogen desorption plateau pressure of vanadium hydrides, V-3A binary alloys (i.e. V 97 Al 3 , V 97 Mn 3 , and V 97 Ru 3) were prepared by vacuum arc melting. Hydrogen absorption and desorption properties of the newly prepared V-3A samples were studied, and compared to vanadium hydrides, by pressure-composition-temperature measurements and first-principles calculations. Among V-3A binary alloys, V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 48 publications
(43 reference statements)
0
7
1
Order By: Relevance
“…In the former, during the absorption and desorption processes, chemical bonds need to be broken and formed, affecting the (de)hydrogenation kinetics. [5][6][7] For the latter, highly porous open structures decorated with lightweight metal atoms, with an effort to improve their interactions with hydrogen molecules [8][9][10], attracted significant interest in recent years. [11][12][13][14] Among these are the metal decorated, atomically thin two-dimensional (2D) materials.…”
Section: Introductionmentioning
confidence: 99%
“…In the former, during the absorption and desorption processes, chemical bonds need to be broken and formed, affecting the (de)hydrogenation kinetics. [5][6][7] For the latter, highly porous open structures decorated with lightweight metal atoms, with an effort to improve their interactions with hydrogen molecules [8][9][10], attracted significant interest in recent years. [11][12][13][14] Among these are the metal decorated, atomically thin two-dimensional (2D) materials.…”
Section: Introductionmentioning
confidence: 99%
“…Most information on pure V is available for the transformation toward the dihydride, VH 2 : Ono reported a ∆H of 49.4 kJ/mol [28], while Reilly reported a ∆H of 40 ± 1 kJ/mol [29]. Liu et al measured the ∆H and ∆S of about 39.6 kJ/mol and 120 J/(mol K) for pure V and revealedthat these values tended to decrease with a partial replacement of V by 3 at% of Al, Mn e Ru [6]. Griffiths et al reported the enthalpy variation for the hydrogenation of pure vanadium for a low hydrogen content (H/M < 0.03) in the α (solid solution) phase.…”
Section: Hydrogen Absorption/desorptionmentioning
confidence: 99%
“…When measuring the pressure composition isotherms, one can observe various pressure plateaus; however, the one corresponding to the transition from the solid solution (α phase) to VH 0.5 has an extremely low pressure, on the order of 1 mbar [3,4]; therefore, it is extremely difficult to remove hydrogen at low hydrogen concentrations. One way to partially mitigate the irreversible storage of hydrogen in vanadium is the partial substitution of V with other metals, such as Ti, Cr, Ni, Fe, etc., which generally leads to a higher equilibrium pressure and a sloping plateau [3,[5][6][7] in the pressure composition isotherms.…”
Section: Introductionmentioning
confidence: 99%
“…Reversible metal hydrides show upon hydrogenation a substantial volume change, e.g. up to about + 40% for V ⟶ VH 2 , 1 which is an important safety aspect to consider in the design of metal hydride tanks. However, the powdery, transient nature of metal hydride beds makes the measurement of such expansion forces not trivial; 2 compaction into pellets is not a remedy since the additional compression energy put into the material makes its presence forcibly felt once the system runs through sorption cycles hence it may even aggravate the issue.…”
Section: Introductionmentioning
confidence: 99%